Gauge invariance and covariant Reggeization - Jones,HF; Scadron,MD; Gault,FD (Il Nuovo Cimento A, 1970)
By the use of gauge-invariant couplings the formalism of covariant Reggeization is extended to deal with processes involving photons. Particular attention is paid to pion photoproduction, where Reggeized pion and nucleon exchange are shown to connect smoothly on to the elementary exchanges both from the form of the vertex couplings and form their respective contributions to the invariant amplitudes. In the latter approach the double-pole structure of the Coulomb Born terms is correctly reproduced. Pion Compton scattering is also studied as an archetypal two-photon process: here the problem of Pomeron Reggeization is similarly resolved. The Froissart-Gribov continuation is briefly discussed, as is the forward peak in π+ photoproduction. © 1970, Società Italiana di Fisica. All rights reserved.